Probing true creep-hardening interaction in weld simulated heat affected zone of P91 steels. (October 2019) - Akhtar, Modassir; Khajuria, Akhil
Highlights: Creep-damage was divided into four classes at sub-HAZs of P91 and P91B steels. PWHT was effective in reducing hardness by 50%. Decreased hardness led to grain boundary and sub-grain boundary hardening and final hardness came in the proximity of parent metals. Grain boundary and sub-grain boundary embrittlement dominates in P91 steel. The increase in prior-austenite grain size motivates creep-damage in P91 steel in comparison to P91B steel. Abstract: The inducement of this paper was to discuss the novel perspective in establishing true creep-hardening interaction at room temperature by hardness and at high temperature by impression creep testing in two boron modified P91 steels. Different sub-heat affected zones (HAZs) were physically simulated. Their creep-strengths were governed by heat treatment, grain-size, hardness, boron addition, and microstructural stability. Post weld heat treatment resulted in reduction in hardness by 50% whereas, impression creep testing showed enhanced creep-strength (50–77%) and the narrow band of creep-damage (∼57%) in P91B steel than P91 steel. An increase in creep-rate with the increase in prior-austenite grain size showed grain boundary embrittlement in P91 steel. Whereas, with an increase in creep-rate and the corresponding decrease in prior-austenite grain size showed grain boundary and sub-grain boundary hardening in P91B steel. Furthermore, type-IV (fine-grain HAZ) and type-III (coarse-grain HAZ) failures were observed depending upon critical prior-austenite grain size of 17 μm in P91 and P91B samples respectively. Based on prior-austenite grain size and creep-strength, sub-HAZs were classified into different classes pursuant to the nature of creep-damage and discussed systematically. Grain boundary hardening was ineffective for both coarse + fine grain HAZ (CF) and B-CF due to the locking movement of fine-grains. However, the formation of soft ferrite grains weakens both coarse + inter-critical HAZ (CI) and B-CI. This study provided better understanding of failure mechanisms in P91 and P91B steels that results in the delay of failures of power plant components.